Bitcoin Adoption and Beliefs in Canada. A Comment on Daniela Balutel, Christopher Henry, Jorge Vásquez, and Marcel Voia (Canadian Journal of Economics, 2022) - Leo Van Hove (Journal of Comments and Replications in Economics (JCRE), 2025)
This comment shows that the empirical part of Balutel et al.'s (2022a) article suffers from an internal validity problem. Specifically, their network size variable is problematic. Hence, Balutel et al. fail to provide reliable evidence that network effects impact Bitcoin adoption.
https://doi.org/10.15456/j1.2025169.1141885422
Keywords: D83; O33; 330; Bitcoin; Adoption; Network effects